SIFAT KIMIA TANAH DAN PRODUKTIVITAS KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TINGGI MUKA AIR TANAH YANG BERBEDA DI LAHAN GAMBUT - Wawan Wawan; Erlida Ariani; Heru Rahmatsyah Lubis (Jurnal Agroteknologi, 2019)
The aims of this study to be determine the soil chemical properties and productivity of oil palm (Elaeis guineensis Jacq.) at different water levels on peatlands. The research was carried out in PT. Tabung Haji Indo Plantation (PT. THIP) Indragiri Hilir and the analys of soil chemical properties were conducted at the Laboratory of Soil Science, Faculty of Agriculture, Universitas Riau, Tampan District, Pekanbaru. This research was held started July to October 2017. This research conducted used survey method. The sampling location in this research are divided into 3 strata in 3 difference blocks and 3 samples that had been determined are named: TMA1 = 20- 40 cm, TMA2 = 41-60 cm and TMA3 => 60 cm carried out experimental used completely randomized design (CRD). There are three times repeatation treatments and 27 samples units in total. The observation data that obtained are analyzed statistically using analysis of variance (ANOVA). The results of variance analysis were continued by Duncan's multiple range test at the 5% level. The parameters of observation carried out include soil chemical properties: pH, C-organic, N-total, P-total, K-total, cation exchange capacity (CEC), saturation of bases (KB) and productivity of oil palm. The results showed that peatland with a water level of > 60 cm had soil pH, organic C, N-total, P-total, K-total, and CEC was higher than the water level of 20-40 cm and 41-60 cm, while KB at a depth of 20-40 cm had a higher KB value than the water level of 41-60 cm and > 60 cm.